2018
DOI: 10.1038/s41467-018-06059-7
|View full text |Cite
|
Sign up to set email alerts
|

Role of dimensional crossover on spin-orbit torque efficiency in magnetic insulator thin films

Abstract: Magnetic insulators (MIs) attract tremendous interest for spintronic applications due to low Gilbert damping and the absence of Ohmic loss. Spin-orbit torques (SOTs) on MIs are more intriguing than magnetic metals since SOTs cannot be transferred to MIs through direct injection of electron spins. Understanding of SOTs on MIs remains elusive, especially how SOTs scale with the MI film thickness. Here, we observe the critical role of dimensionality on the SOT efficiency by studying the MI layer thickness-depende… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
86
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(92 citation statements)
references
References 40 publications
6
86
0
Order By: Relevance
“…Note that the counterclockwise and clockwise switching under positive and negative charge currents, respectively, is opposite compared to Ta/CoFeB and W/CoFeB systems due to an inversion of the stacking sequence of HM and FM layers. Our observations are also consistent with the observed SOT switching in a Tm 3 Fe 5 O 12 /Tungsten (TMIG/W) heterostructure as reported before, since W in their experiments and Ta in our experiments exhibit a spin Hall angle with the same polarity. On the other hand, no such R AHE loops are observed while sweeping H y (Figure d).…”
supporting
confidence: 93%
See 3 more Smart Citations
“…Note that the counterclockwise and clockwise switching under positive and negative charge currents, respectively, is opposite compared to Ta/CoFeB and W/CoFeB systems due to an inversion of the stacking sequence of HM and FM layers. Our observations are also consistent with the observed SOT switching in a Tm 3 Fe 5 O 12 /Tungsten (TMIG/W) heterostructure as reported before, since W in their experiments and Ta in our experiments exhibit a spin Hall angle with the same polarity. On the other hand, no such R AHE loops are observed while sweeping H y (Figure d).…”
supporting
confidence: 93%
“…Due to the semiconducting nature and low Curie temperature of CGT, direct electrical characterization of its magnetization has proven to be difficult, and most of the studies on CGT have utilized magneto‐optic Kerr effect (MOKE) or magnetic force microscopy (MFM) . A stack consisting of HMs such as Pt or W deposited on an insulating FM such as Tm 3 Fe 5 O 12 (TMIG) has shown to result in an induced anomalous Hall effect in the metal, thus providing an electrical path toward reading the magnetization of insulating FMs . In fact, a recent study has used a similar approach to characterize a CGT/Pt heterostructure .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It has been demonstrated that the spin current generated in the Pt layer could switch the magnetization of the FGT layer by exerting a damping‐like spin‐orbital torque. Comparing with prior switching devices, a better switching efficiency of 2.2 has been found in this case . According to Figure E, the critical current density required to switch the FGT magnetization strongly depends on the magnitude of an in‐plane applied magnetic field …”
Section: Progress On Van Der Waals Magnets and Heterostructuresmentioning
confidence: 66%